Research on the Compactness of Lunar Soil Simulant Based on Static Cone Penetration Test - Yuxin Zhang; Hui Gao; Xiaohong Fang; Shuting Xing; Long Xiao; Longchen Duan (Applied Sciences)
The shear strength and bearing characteristics of lunar soil have a strong connection with its compactness. The compactness varies significantly with depth and has an important effect on engineering activities on the lunar surface. In this study, lunar soil simulant samples of four compactness levels were prepared to explore the relationship between compactness and cone tip resistance in static cone penetration tests (CPTs). The compactness values at different depths were measured layer by layer, and CPTs were carried out. The results indicate that the cone tip resistance continuously increases with the increase in the penetration depth until it reaches a peak, and then remains constant for a certain depth. The cone tip resistance after the normalization of the overburden stress gradually increases and then decreases after reaching the peak. Models of the relationship between cone tip resistance before and after normalization and compactness were constructed using a regression algorithm. The variation in lunar soil compactness with depth can be determined by measuring cone tip resistance with this model. The research findings can provide a theoretical basis for in situ testing, site selection for lunar bases, and other related aspects on the lunar surface.